Clinical characteristics of triple-negative breast cancer: experience in an Asian developing country. - Tan, G.H.; Taib, N.A.; Choo, W.Y.; Teo, S.H.; Yip, C.H. (West Asia Organization for Cancer Prevention, 2009)
The incidence of TN breast cancer in our study is similar to other studies, and associated with a higher grade.